Switching effective oxygen reduction and evolution performance by controlled graphitization of a cobalt–nitrogen–carbon framework system. Issue 5 (18th April 2016) - Gadipelli, Srinivas; Zhao, Tingting; Shevlin, Stephen A.; Guo, Zhengxiao
Abstract : Effective oxygen reduction/evolution nanoporous cobalt–nitrogen–carbon based catalysts are developed from rationally designed single-precursor Co x Zn100− x –ZIF-8 with controlled graphitization. Abstract : We report a purposely designed route for the synthesis of a promising carbon-based electrocatalyst for both ORR (oxygen reduction reaction) and OER (oxygen evolution reaction) from zeolitic imidazolate frameworks (ZIFs). Firstly, precursor ZIFs are rationally designed with a blend of volatile zinc to induce porosity and stable cobalt to induce graphitic domains. Secondly, the self-modulated cobalt–nitrogen–carbon system (SCNCS) is shown to be an effective ORR catalyst after graphitization at mild temperatures. Finally, the best OER catalyst is developed by enhancing graphitization of the SCNCS. For the first time, solely by switching the graphitization conditions of SCNCS, excellent ORR or OER performance is realized. This approach not only opens up a simple protocol for simultaneous optimization of nitrogen doping and graphitization at controlled cobalt concentrations, but also provide a facile method of developing such active catalysts without the use of extensive synthesis procedures.